1988
DOI: 10.2307/1242074
|View full text |Cite
|
Sign up to set email alerts
|

Education, Experience, and Allocative Efficiency: A Dual Approach

Abstract: A generalization of the dual, non‐frontier profit function approach to evaluating allocative efficiency is developed that allows for training (human capital) variables to influence the efficiency level directly. An application to Pennsylvania dairy indicates that education and experience are substitutes and play a significant role in the level of efficiency. While these operators are not allocating their variable inputs in an absolutely efficient manner, relative efficiency can be achieved for four of six poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 13 publications
2
32
1
1
Order By: Relevance
“…The hypothesis that educated farmers and lowland management experience have a negative effect on allocative inefficiency is rejected. This is not consistent with the finding of Stefanou and Saxena (1988) who found that operators of dairy farms in Pennsylvania with postsecondary education demonstrated a greater degree of flexibility in the allocation of variable inputs. The significant effect of the joint interaction of water control and lowland farming systems (TybasRFS and TybasRVFS) on allocative inefficiency indicates that the level of irrigation and lowland farming systems are complements and also play a significant role in allocative efficiency.…”
Section: Truncated Bootstrap Analysis Of Sources Of Inefficiencycontrasting
confidence: 99%
See 2 more Smart Citations
“…The hypothesis that educated farmers and lowland management experience have a negative effect on allocative inefficiency is rejected. This is not consistent with the finding of Stefanou and Saxena (1988) who found that operators of dairy farms in Pennsylvania with postsecondary education demonstrated a greater degree of flexibility in the allocation of variable inputs. The significant effect of the joint interaction of water control and lowland farming systems (TybasRFS and TybasRVFS) on allocative inefficiency indicates that the level of irrigation and lowland farming systems are complements and also play a significant role in allocative efficiency.…”
Section: Truncated Bootstrap Analysis Of Sources Of Inefficiencycontrasting
confidence: 99%
“…However, Huffman (1974) reported that the contribution of education is only an 'allocative effect'. Stefanou and Saxena (1988) found that education may enhance the farmer's ability to allocate inputs efficiently across competing uses, and contribute to good farm planning. Therefore, it was assumed in this study that the variable EDUC had a negative effect on technical, allocative and scale inefficiency.…”
Section: Second Stage Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This result shows that human capital accumulation contributes to improving efficiency. The positive impact of human capital such as education, agricultural experience and training on efficiency in agricultural production has been widely confirmed (Kaliranjan & Shand, 1985;Stefanou & Saxena, 1988;Gorton & Davidova, 2004;Solí s, Bravo-Ureta, & Quiroga, 2009). For olive farms in Tunisia, Lachaal et al (2004Lachaal et al ( , 2005 found a positive relationship between the share of skilled labor and technical efficiency.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Regarding the factors affecting efficiency, many studies consider human capital as one of the determinants of agricultural production (Kaliranjan & Shand, 1985;Stefanou & Saxena, 1988;Gorton & Davidova, 2004). For olive production in Tunisia, a positive effect of human capital on efficiency was confirmed by Lachaal et al (2004) and Lachaal et al (2005), which represented human capital as a share of skilled labour.…”
Section: Modelmentioning
confidence: 99%